HUBUNGAN DETERMINASI DIRI DAN EFIKASI DIRI DENGAN PENGAMBILAN KEPUTUSAN KARIR PADA SISWA SMK - Uki Ritmadanti; Kusnarto Kurniawan (IKIP Siliwangi, 2026)
Today's teenagers are experiencing difficulties in making career decisions, as evidenced by their confusion in determining their future career choices. This study aims to examine the relationship between self-determination and self-efficacy with career decision-making among 12th grade students at SMK Negeri 9 Semarang. This study used a correlational quantitative design with data collection techniques using the career decision-making scale (Tiedeman & O'Hara), self-determination scale (Ryan & Deci), and self-efficacy scale (Bandura) with a Likert model. The population consisted of 351 students and the sample consisted of 187 students using probability sampling with proportionate stratified random sampling technique. The validity and reliability test results for the career decision-making instrument (0.904), self-determination (0.832), and self-efficacy (0.881) were declared valid and reliable. The data analysis technique used multiple linear regression. Self-determination influenced career decision-making with a significance value of 0.023 < 0.050, and self-efficacy also influenced career decision-making with a significance value of 0.000 < 0.050. Simultaneously, both have an influence of 16.8% with a significance value of 0.000 < 0.050, while the remaining 83.2% is influenced by other variables. It can be concluded that the higher the self-determination and self-efficacy of students, the more likely they are to improve their career decision-making abilities.